2012
DOI: 10.3389/fnevo.2012.00008
|View full text |Cite
|
Sign up to set email alerts
|

Learning to read aligns visual analytical skills with grapheme-phoneme mapping: evidence from illiterates

Abstract: Learning to read puts evolutionary established speech and visual object recognition functions to novel use. As we previously showed, this leads to particular rearrangements and differentiations in these functions, for instance the habitual preference for holistic perceptual organization in visual object recognition and its suppression in perceiving letters. We performed the experiment in which the differentiation between holistic non-letter processing and analytic letter processing in literates was originally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 50 publications
1
24
1
2
Order By: Relevance
“…Thus, as in the case of memory research, literacy may improve face perception rather than being detrimental. Note also that the Lachmann et al (2012) findings do not mean that readers have lost the ability to process letters holistically. van Leeuwen and Lachmann (2004) have shown that contrasting strategies of holistic processing in shapes and analytic processing for letters resulted in uniformly holistic processing if task demands required it.…”
Section: Can Literacy Be Detrimental?mentioning
confidence: 89%
“…Thus, as in the case of memory research, literacy may improve face perception rather than being detrimental. Note also that the Lachmann et al (2012) findings do not mean that readers have lost the ability to process letters holistically. van Leeuwen and Lachmann (2004) have shown that contrasting strategies of holistic processing in shapes and analytic processing for letters resulted in uniformly holistic processing if task demands required it.…”
Section: Can Literacy Be Detrimental?mentioning
confidence: 89%
“…Lachmann, Khera, Srinivasan, & van Leeuwen, 2012;Lachmann & van Leeuwen, 2008). Note that the visual routines supporting object recognition that humans have acquired during evolution can actually impede reading acquisition.…”
Section: Mirror Invariancementioning
confidence: 99%
“…Consequently, the different features of the characters cannot rapidly be bound into a single object (see Lachmann, Khera, Srinivasan, & van Leeuwen, 2012). Consequently, the different features of the characters cannot rapidly be bound into a single object (see Lachmann, Khera, Srinivasan, & van Leeuwen, 2012).…”
Section: Letter-position Coding In Unfamiliar Orthographies: New Evidmentioning
confidence: 99%